PENGARUH LITERASI KEUANGAN, EFIKASI DIRI KEUANGAN, PENGGUNAAN FINTECH TERHADAP MANAJEMEN KEUANGAN MAHASISWA S1 AKUNTANSI UNIVERSITAS WIJAYA KUSUMA SURABAYA - Merlin Maharani; Mega Rosdiana (CV. Denasya Smart Publisher, 2026)
The advancement of digital technology has substantially influenced student financial management, including that of Accounting students; however, their financial knowledge is not always effectively applied in daily life. Limited financial literacy, low financial self-efficacy, and underdeveloped use of financial technology may negatively impact the quality of students' financial management. This study aims to examine the effects of financial literacy, financial self-efficacy, and fintech utilization on the financial management of undergraduate Accounting students at Wijaya Kusuma University, Surabaya. A quantitative, associative research design was employed. Data were collected through questionnaires distributed to 100 purposively selected respondents. Multiple linear regression analysis was conducted after the data met validity, reliability, and classical assumption requirements. The findings indicate that financial literacy and financial self-efficacy exert a positive and significant influence on student financial management, whereas fintech utilization does not have a significant effect. Collectively, the three independent variables significantly affect student financial management. The study concludes that enhancing financial literacy and strengthening financial self-efficacy are crucial for fostering more structured financial management among students